The effect of work motivation on performance with job satisfaction as an intervening variable in the Faculty of Economics and Business, UIN Walisongo Semarang - Nurudin Nurudin (Journal of Islamic Economics, Management, and Business (JIEMB), 2020)
Purpose – This study aims to determine the effect of work motivation on performance with job satisfaction as an intervening variable.Method – The population in this study were all employees at the Faculty of Islamic Economics and Business UIN Walisongo Semarang with a total sample of 58 respondents. The analysis in this study uses path analysis technique.Result – The results showed that work motivation had a significant effect on job satisfaction, work motivation had a significant effect on performance and job satisfaction variables had a significant effect on performance. The results of the path analysis conducted showed that work motivation had a direct effect on employee performance, while work motivation had an indirect effect on performance through intervening work.Implication – This study assists the management of higher education to create working design for a better performance.Originality – This study enriches the empirical study of job performance in higher education context in Indonesia.